Features and prognostic utility of biopsy in oral squamous cell carcinoma. (24th December 2015) - Dhanda, Jagtar; Uppal, Nugdeep; Chowlia, Harpreet; Opie, Neil; Al‐Qamachi, Laith; Shelat, Devesh; Aslam, Adil; Yuffa, Arie; Martin, Timothy; Risk, Janet; Triantafyllou, Asterios; Shaw, Richard; et al.
Abstract: Background: Traditional approaches in oral squamous cell carcinoma (OSCC) management utilize biopsy tissue for diagnostic purposes only. Adverse prognostic features, such as the tumor depth, are usually determined from final resection specimens, but are seldom studied in biopsy tissue. Methods: A preliminary study of 139 consecutive biopsies compared biopsy size with T classification, tumor site, and operator grade, and biopsy tumor depth with the true tumor depth. Results: This study demonstrated that biopsy size is independent of T classification ( p = .44), subsite ( p = .86), and operator grade ( p = .10). The biopsy tumor depth significantly underrepresented true tumor depth (2.5 mm, 95% confidence interval [CI] = 2.4–2.9 vs 8.2 mm, 95% CI = 6.5–9.9; p < .001), confirming the limited prognostic utility of biopsies in OSCC. Conclusion: A future clinical trial will compare the routine biopsy technique with standardized deeper biopsy techniques using punch biopsy to sample invasive fronts and investigate opportunities for up‐front staging using a combination of histological features and epithelial and stromal molecular biomarkers in OSCC. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1857–E1862, 2016